Low-energy direct muon transfer from H to Ne10+, S16+ and Ar18+ using the two-state close-coupling approximation to the Faddeev-Hahn-type equation - Sultanov, R. A.; Adhikari, S. K. (Iop Publishing Ltd, 2002)
We perform a three-body calculation of direct muon-transfer rates from thermalized muonic hydrogen isotopes to bare nuclei Ne10+, S16+ and Ar18+ employing integro-differential Faddeev-Hahn-type equations in configuration space with a two-state close-coupling approximation scheme. All Coulomb potentials including the strong final-state Coulomb repulsion are treated exactly. A long-range polarization potential is included in the elastic channel to take into account the high polarizability of the muonic hydrogen. The transfer rates so-calculated are in good agreement with recent experiments. We find that the muon is captured predominantly in the n = 6, 9 and 10 states of muonic Ne10+, S16+ and Ar18+, respectively.